Education Financing Strategies: SWOT Analysis for Sustainable Strategy - Hermansyah Hermansyah; Usfandi Haryaka; Ranto Setiyono; Endry Setiawan; Arina Santi; Ninik Handayani (Universitas Muhammadiyah Enrekang, 2024)
This study aims to analyze education financing strategies by using SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis to identify the strengths, weaknesses, opportunities, and threats faced by schools. The main strengths found are the existence of canteens and cooperatives as sources of internal income, the participation of employees and students in school financing, and support from committees, parents, and alumni. The weaknesses identified include limited human resources in managing financing, costs for competitions, procurement of facilities and infrastructure, as well as salaries for teachers and honorary staff. Opportunities that can be used include regular funds from the government and local governments as well as contributions from committees and alumni. The threats faced include delays in the procurement of the 2013 Curriculum books and dependence on the procurement of civil servants. The proposed way of solving the problem is through an alternative strategy designed based on a SWOT analysis. This strategy includes leveraging internal strengths and external opportunities to increase school revenues, improving internal weaknesses through better training and management, and addressing threats by seeking more independent and innovative alternative solutions. The results of the study show that with the right strategy, schools can improve the effectiveness of education financing, ensure optimal use of resources, and achieve desired educational goals. This research also highlights the importance of careful planning and collaboration with various stakeholders to ensure sustainability and improve the quality of education in schools.